Implementación de un sistema contable y su repercusión en el manejo de la información en el calzado "Original Sport" el Cantón Ventanas Provincia de Los Ríos año 2011 - Quijije Moncada, Karina Antonieta (2012)
This research concerns the "Implementation of an accounting system and its impact on the management of information in the Original Sport Shoe", aims to design a useful tool to facilitate the accounting process that is carried in this company. The research project will facilitate the improvement of accounting processes and agile and timely submission of financial information shoe "Original Sport". In the development of the investigation it was determined that the shoe does not have a tool that provides mechanized and automated accounting and financial information that is timely, reliable, concise, verifiable, objective, useful and truthful. This is due to the lack of an appropriate accounting system We propose the development of an accounting system for footwear, serving to help the homeowners to be carried out with excellence all their goals in the shortest time possible. The proposal is feasible since besides being a base and consultation, will optimize the financial and administrative resources of the shoe.